Modified Foam Stability Test (Fs-50) as Predictor of Fetal Lung Maturity in Preterm Premature Rupture of Membrane Patients Given Dexamethasone Therapy - Olivia Listiowati Prawoto; Tjokorda Gde Agung Suwardewa; I Made Darmayasa; Putu Doster Mahayasa; I Nyoman Bayu Mahendra; Evert Solomon Pangkahila (Syntax Corporation Indonesia, 2023)
This study aims to determine the ability of the Modified Foam Stability (FS-50) test to predict fetal lung maturity in preterm premature rupture of membranes treated with Dexamethasone. The study sample included pregnant women with PROM at a gestational age of 24 to less than 34 weeks in the ER and Obstetrics Ward of Sanglah Central General Hospital, Denpasar. The patient underwent a vaginal speculum examination to collect fluid pooled in the vagina or from the outer cervical opening. Fluids are checked with the Modified Foam Stability (FS-50) test and graded from 0 to +4 to estimate fetal lung maturity. The first test was performed before Dexamethasone, followed by serial examinations at 12-hour intervals for 48 hours. Before dexamethasone injection, all patients got 0 scores as a baseline. There were statistically significant differences in FS-50 values before and after injection of the first, second, third, and fourth doses of Dexamethasone in PPROM patients. Fetal lung maturity was reached after the third dose of dexamethasone injection (36 hours after the first injection), characterized by an FS-50 value of > +3 and no asphyxia in the newborn. Spearman's rank analysis showed a significant correlation (p=0.005) between infants' maximum FS-50 value and asphyxia status. The FS-50 value > +3 is associated with the absence of asphyxia in infants born to PPROM patients who were given Dexamethasone for lung maturation. FS-50 can predict fetal lung maturity in preterm premature rupture of membranes given dexamethasone therapy.